Peran Komisi Pemberantasan Korupsi Dan Kepolisian dalam Pemberantasan Tindak Pidana Korupsi di Indonesia dalam Perspektif Teori Sistem Hukum - Muwahid, Muwahid; Hayya , Akiya Qidam; Putri , Tiara Intan (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2021)
This article discusses the role of the Corruption Eradication Commission and the Police in eradicating corruption in Indonesia from the perspective of legal system theory. This research is normative legal research, using legislation, conceptual, and case approaches. Legal materials are obtained from laws and regulations, law books, legal journals, and related articles, then analyzed using deductive thinking patterns, namely drawing general things to draw a specific conclusion. The study results indicate that the Corruption Eradication Commission and the Police are included in sub-systems of criminal justice, both of which have the authority to enforce the law in the field of corruption per the authorities stipulated in the legislation. From the legal system theory perspective, the enforcement of criminal acts of corruption must be seen from three aspects, namely the laws and regulations, law enforcement officers, and the legal culture of the community. From these three aspects, the Corruption Eradication Commission and the Police have a very decisive role in law enforcement for corruption under their respective authorities.